Plasma concentration of MMP-17 is elevated in boys with cryptorchidism and correlates with HSP-70 - Małgorzata Kowalska; Marzena Tylicka; Olga Martyna Koper-Lenkiewicz; Joanna Kamińska; Justyna Dorf; Ewa Matuszczak (Scientific Reports)
Abstract Cryptorchidism, the absence of one or both testicles in the scrotum, is the most common anomaly of genitourinary tract in males. The pathogenesis of undescended testes is unknown however the role of inflammation, tissue remodeling and oxidative stress is postulated. The aim of this study was to explore the role of HSP-70, MMP-3, MMP-17 and IL-8 in possible pathogenic pathways connected with cryptorchidism. Cryptorchid patients with high scrotal and inguinal canal localization were included. The study group consisted of 63 patients aged 12–24 months, whereas the control group included 17 healthy infants with the same demographic characteristics. The analysis of plasma samples was carried out using ELISA enzyme-linked immunosorbent assay technique. The plasma concentration of MMP-17 in boys with cryptorchidism was significantly higher compared to the control group (p = 0.0365). The concentration of plasma IL-8, MMP-3, and HSP-70 in boys with cryptorchidism increased in comparison to the control group but these increases were not statistically significant (p > 0.05). A positive correlation was found between plasma MMP-17 and HSP-70 concentration (r = 0.5153; p < 0.0001). Our results demonstrate that MMP-17 and HSP-70 might be involved in pathogenesis of cryptorchidism and are in line with current knowledge that high temperature has a negative influence on male gonads.